Old age facilities for German-speaking people in Thailand – a new facet of international migration in old age. Issue 7 (18th May 2020) - Bender, Désirée; Hollstein, Tina; Schweppe, Cornelia
ABSTRACT: This article examines old age facilities in Thailand catering to people from German-speaking countries. These institutionalised spaces of age(ing) in the 'Global South' represent a new facet of migration in old age. Starting with the question of what motivates people to migrate in old age and to opt for these facilities in Thailand, the article identifies important factors that characterise what these facilities offer and shows the compatibility that exists between these offerings and the heterogeneous needs and aspirations of the older migrants. Transnational intertwinements between Thailand and the Germanophone countries of origin characterise many of the specific features of these facilities, which allow them to present multiple perspectives for extended life options for ageing people from German-speaking countries. They provide institutionalised responses to a range of different hopes and unmet needs associated with the prospect of growing (and being) older while remaining in the country of origin, and at the same time, they address the challenges and potential risks of the migration process.